Kurikulum 2013 dan Relevansi Pembelajaran HOTS di Sekolah; (Tinjauan Teoritis Pendidikan Terhadap Pembelajaran Abad XXI) - Mukmin Mukmin; Isna Radiyah; Budi Yusuf (AZKIYA, 2021)
XXI Century Education experienced a paradigm change because it was influenced by the response of the world of education to the Industrial Revolution 4.0. On the other hand, the Industrial Revolution 4.0 helped encourage the birth of the Educational 4.0 era which was perceived by many parties as an era of the use of digital technology in the learning process, or known as the cyber system) which was able to make the learning process continuously without limit of space and time. The Indonesian government's policy to implement the 2013 curriculum (K-13) in learning is the answer to various expectations for various skills that must be possessed by learners in the XXI century. Learning is termed with 4C (Communication, Collaboration, Critical Thinking and Problem Solving, Creativity and Innovation) which is the real ability to go to the K-13 learning. This goal is certainly only able to be realized if the learning is done at school using high-level thinking skills (Higher Order Thingking Skills/HOTS) which is defined as the wider use of thoughts to find new challenges.